Assessment of a numerical strategy for fatigue growth and shape evolution of a corner crack from a pin-loaded hole. (September 2021) - Bovecchi, F.; Boni, L.; Fanteria, D.; Lazzeri, L.
Abstract: The study investigates fatigue growth and shape evolution of a corner crack in a pin-loaded hole by means of three-dimensional FE analyses. The constraint factor/plasticity-induced crack closure strategy was tuned to reproduce experimentally measured crack front shapes. The study quantitatively determines the LEFM acceptability regions using elastic–plastic simulations. It also assesses the sensitivity of crack propagation and shape evolution to the stress distribution along the front, to the relationship between J-integral and stress intensity factor, and to changing propagation rates along different directions. The proposed approach produces very accurate results in terms of crack propagation rate and shape evolution. Highlights: Fatigue crack growth of a pin-loaded hole corner crack is investigated. Constraint factor/plasticity-induced crack closure is tuned to capture crack shapes. Elastic–plastic simulations are used to determine the constraint factor distribution. Sensitivity to changing propagation rates along different directions is assessed.